2014
DOI: 10.1136/jclinpath-2013-202114
|View full text |Cite
|
Sign up to set email alerts
|

WT1 expression increases with malignancy and indicates unfavourable outcome in astrocytoma

Abstract: The significant WT1 expression differences between diffuse astrocytomas, oligoastrocytomas and oligodendrogliomas, which are also present in the Repository for Molecular Brain Neoplasia Data, National Cancer Institute (REMBRANDT, 2005, http://rembrandt.nci.nih.gov) gene database set, provide a rationale for use of WT1 as part of a routine immunohistochemistry panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…12,23 This differential expression of WT1 in high-grade brain tumors has recently been validated in an in vivo study analyzing human gliomas, which included 442 glioblastomas, 303 astrocytomas, 41 oligodendrogliomas, and 43 oligoastrocytomas. 27 The results showed that WT1 expression in brain tumors increased with WHO grade, older age, and absence of IDH1 mutation. 27 The introduction of a WT1-based vaccine in clinical trials was first described by Oka et al in 2004.…”
Section: Gbm and Wilms Tumormentioning
confidence: 93%
See 1 more Smart Citation
“…12,23 This differential expression of WT1 in high-grade brain tumors has recently been validated in an in vivo study analyzing human gliomas, which included 442 glioblastomas, 303 astrocytomas, 41 oligodendrogliomas, and 43 oligoastrocytomas. 27 The results showed that WT1 expression in brain tumors increased with WHO grade, older age, and absence of IDH1 mutation. 27 The introduction of a WT1-based vaccine in clinical trials was first described by Oka et al in 2004.…”
Section: Gbm and Wilms Tumormentioning
confidence: 93%
“…27 The results showed that WT1 expression in brain tumors increased with WHO grade, older age, and absence of IDH1 mutation. 27 The introduction of a WT1-based vaccine in clinical trials was first described by Oka et al in 2004. 13,25 The authors reported the effects of the vaccine on breast cancer, lung cancer, and leukemia in 26 patients, reporting tumor regression and no toxicity as a result of the drug.…”
Section: Gbm and Wilms Tumormentioning
confidence: 93%
“…According to the WHO classification of central nervous system tumors, glioma is divided into four different grades depending on the malignant potential. Immunohistochemical analyses demonstrated that WT1 is expressed in many gliomas (5,(26)(27)(28)(29) (Figure 1) and expression is variable depending on the tumor grade. In less-aggressive grade II glioma and diffuse astrocytoma, WT1 expression was lower than that in grade IV glioblastoma.…”
Section: Gliomamentioning
confidence: 99%
“…In less-aggressive grade II glioma and diffuse astrocytoma, WT1 expression was lower than that in grade IV glioblastoma. Furthermore, Rauscher et al (29) reported that WT1 expression is a prognostic marker of WHO grade II and III tumors, and WT1 expression is reduced in recurrent tumors.…”
Section: Gliomamentioning
confidence: 99%
See 1 more Smart Citation